Validity of the Creasy risk appraisal instrument for prediction of preterm labor. - Edenfield SM; Thomas SD; Thompson WO; Marcotte JJ (Nursing Research)
The study objectives were twofold: (a) retrospective evaluation of the predictive validity of the Creasy in a cross-cultural urban and rural population based on the outcome data of publicly served prenatal patients, and (b) examination of the universality of the Creasy through comparison of the predictive validity found in the study population with other published results. Subjects were 433 white and African American women who entered prenatal services through 1 urban and 12 rural health department sites and received care in a regionalized system in East Central Georgia. The Creasy instrument was administered once to all prenatal women in their initial clinical encounters. The instrument identified 30.47% of the women who experienced preterm deliveries. Only 44.3% of the time did a score indicating high risk for preterm delivery accurately predict preterm delivery. Predictive validity for rural and urban subjects was not significantly different. As predictive validity for the Creasy was low, it was determined that it has limited clinical usefulness with a single administration. Usefulness may be improved with further risk-factor specification and frequent measurement throughout pregnancy.